1981
DOI: 10.1093/infdis/143.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Clostridium difficile from the Environment and Contacts of Patients with Antibiotic-Associated Colitis

Abstract: Clostridium difficile is the most important cause of antibiotic-associated colitis, but its epidemiology remains unknown. Using a selective medium for the isolation of C. difficile, cultures were obtained from the environment and contacts of hospitalized patients carrying C. difficile in their stools. In areas where carriers had diarrhea, 85 (9.3%) of 910 cultures of floors and other surfaces, especially those subject to fecal contamination, were positive. In areas where there were no known carriers, only 13 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
227
0
12

Year Published

1983
1983
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 466 publications
(247 citation statements)
references
References 27 publications
8
227
0
12
Order By: Relevance
“…Person-to-person transmission on hospital wards, especially geriatric wards, as well as environmental contamination and carriage on the hands of hospital workers have been documented (Kim et al, 1981;MalamouLadas et al, 1983;Savage & Alford, 1983;McFarland et al, 1989). Transmission occurs mainly via the faecal oral route and direct contact with contaminated surfaces (Barbut & Petit, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Person-to-person transmission on hospital wards, especially geriatric wards, as well as environmental contamination and carriage on the hands of hospital workers have been documented (Kim et al, 1981;MalamouLadas et al, 1983;Savage & Alford, 1983;McFarland et al, 1989). Transmission occurs mainly via the faecal oral route and direct contact with contaminated surfaces (Barbut & Petit, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental contamination has been suggested as a significant factor in the transmission of C. dificile (Fekety et al, 1980;Larson et al, 1980). Survival of C. dificile in an aerobic environment is possible because this obligate anaerobe can form aerotolerant spores; there are reports that C. dzficile can survive for > 5 months in aerobic conditions (Kim et al, 1981). Although it is well known that C. dificile spores cannot be effectively recovered in ordinary growth medium (Raibaud et al, 1980), their recovery is distinctly enhanced when they are treated with sodium thioglycollate and inoculated in lysozyme containing media (Ionesco, 1978 ;Nakamura et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…N osocomial acquisition and transmission of Clostridium difficile are well known (1)(2)(3)(4). Despite efforts to control and prevent infections in health care facilities, nosocomially acquired C difficile-associated diarrhea (N-CDAD) persists; some have reported that the number of N-CDAD infections are increasing (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%